PENGARUH PENGGUNAAN MEDIA PETA TEMATIK TERHADAP BERPIKIR SPASIAL PESERTA DIDIK PADA MATERI UNSUR CUACA DAN IKLIM DI MAN 1 KOTA BUKITTINGGI - Mirna Erisya; Yurni Suasti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the use of map media on the spatial thinking of students at MAN 1 Bukittinggi City. The research method used in this research is the Quasi Experiment Method with the research design Nonequivalent Control Group Design. Sampling was done by Random Sampling technique. The samples in this study were E6 class students as the experimental class who were given thematic map media treatment and E1 class as the control class who were given general map media treatment. Data collection using pretest and posttest instruments in the form of multiple choice that has been tested for validity, reliability. This study found that there was an effect of map media on the spatial thinking ability of Phase E1 and E6 MAN 1 Bukittinggi students with the average posttest of the experimental class of 90 and the control class of 78. Data analysis using the Paired Sample T-Test test from the calculation data obtained a significance level (Sig.) of 0.000 because the significance is smaller than 0.05 (0.000 <0.05), then Ho is rejected and Ha is accepted.